Understanding the vocational functioning of autistic employees: the role of disability and mental health. Issue 9 (24th April 2023) - Stratton, Elizabeth; Glozier, Nick; Woolard, Alix; Gibbs, Vicki; Demetriou, Eleni A.; Boulton, Kelsie A.; Hickie, Ian; Pellicano, Elizabeth; Guastella, Adam J.
Abstract: Purpose: Employment rates for autistic people are low, despite increasing employment-focused programmes. Given the reported complexities for autistic people in finding and keeping work and flourishing there, further exploration is needed to understand how best to help employers accommodate autistic employees. Material and methods: We assessed 88 employed autistic adults, without comorbid intellectual disability and examined whether self-reported disability and mental health symptoms were associated with two measures of vocational functioning: disability days off work and vocational disability. Results: Nearly half (47%) reported at least one disability day absence in the previous month. Autism severity and IQ were not associated with either measure of vocational functioning. Greater disability and higher mental health symptoms were associated with both types of vocational functioning. However, the associations of anxiety and stress with both vocational outcomes were attenuated to null in a multivariable model. Disability ( B = 6.74, p = 0.009; B = 1.18, p < 0.001) and depression ( B = 4.46, p = 0.035; B = 1.01, p = 0.049) remained independently associated with both outcomes. Conclusions: Clinicians and vocational support programmes addressing modifiable factors may need to focus on addressing mental health comorbidities, specifically depression rather than anxiety, or core features of autism to improve vocational outcomes for autistic people. Implications for Rehabilitation: Individual-level interventions that reduce disablement, particularly in social areas, and depressive symptoms as a way of reducing days off work and improving workplace activities in autistic employees are recommended. Organisations can accommodate autistic employees by encouraging use of mental health programmes or looking at how the workplace environment can be adapted to limit social disability.